2015
DOI: 10.1111/1467-9256.12104
|View full text |Cite
|
Sign up to set email alerts
|

To Know Us is to Love Us: Public Diplomacy and International Broadcasting in Contemporary Russia and China

Abstract: The Soft Power of Hard States, edited by Michael Barr and Valentina FeklyuninaChina and Russia have devoted significant resources to developing their international broadcasting capacity as an instrument of public diplomacy. Focusing on CCTV-N (China) and RT (Russia), this article discusses the strategies each has developed to communicate with international audiences and further the foreign policy ambitions of policy makers in Beijing and Moscow. It highlights the differences between the two stations ? namely C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 13 publications
2
72
1
4
Order By: Relevance
“…But Nye (2004) also suggested that states may accrue "soft power" by using international media to develop a sense of "shared values" across borders (p. 7). As Rawnsley (2015) has observed, this description could easily apply to Chinese and Russian approaches to international broadcasting, which are often regarded in the West as state propaganda.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…But Nye (2004) also suggested that states may accrue "soft power" by using international media to develop a sense of "shared values" across borders (p. 7). As Rawnsley (2015) has observed, this description could easily apply to Chinese and Russian approaches to international broadcasting, which are often regarded in the West as state propaganda.…”
Section: Introductionmentioning
confidence: 92%
“…The conceptual "fuzziness" of "soft power" allowed this journalist to portray the objectives of journalists and politicians as having equal weight within a mutually beneficial relationship. Thus, the journalist's strategic deployment of "soft power" enabled him to avoid dwelling on two profoundly problematic issues: the impossibility of separating "soft" power from "hard" coercive power, and the co-structuring of the BBCWS in relation to state security and intelligence systems (Rawnsley 1996(Rawnsley , 2015.…”
Section: Legitimizing Narratives: Propaganda and Soft Powermentioning
confidence: 99%
“…Det er ikke gjort noen grundige studier som vurderer i hvilken grad RT lever opp til journalistiske normer, men det virker klart at det er stort samsvar mellom offisiell russisk politisk kommunikasjon og RTs nyhetsdekning (Robertson 2015: 26Á28). Det er likevel ingen grunn til å tro at det RT presenterer er en direkte forlengelse av Kremlins politiske kommunikasjon (Rawnsley 2015). Dette er blant annet fordi 5 Ifølge Cull (2009) har offentlig diplomati tradisjonelt stått på fem pilarer: lytting, fremming av eget ståsted, kulturelt diplomati, utvekslingsdiplomati og internasjonal kringkasting.…”
unclassified
“…Firstly, the obscured distinction between soft and hard power, which harks back to the original work of Nye and which is reproduced in theory-centred research, is a recurrent cause for concern among case-centred authors (Rawnsley 2015;Stuenkel 2016;Szostek 2014;Wojciuk et al 2015). Some identify the 'practical difficulty of drawing a clear line between power that is "hard" and power that is "soft"' (Szostek 2014, p. 465) as an unresolved problem in soft-power research, leading others to concede that 'discussions about soft power are inevitably somewhat vague' (Stuenkel 2016, p. 354).…”
Section: Case-centred Researchmentioning
confidence: 99%